Persepsi Siswa terhadap Pembelajaran P5 Berbasis Deep Learning pada Pendidikan Agama Islam di SMA Fajrul Islam - Uswatun Hasanah Sofyan; Sarah Sakhowah; Randy Zahran; Al Fathir Rahman Zulkarnain (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to explore students’ perceptions of the implementation of the Pancasila Student Profile Reinforcement Project (P5) based on deep learning within the Islamic Religious Education (PAI) subject at SMA Fajrul Islam. This research employs a descriptive qualitative method with data collected through in-depth interviews, observations, and documentation. Interviews were conducted with 10 students from grades X and XI. The findings indicate that students perceive the deep learning–based P5 as a more meaningful and enjoyable learning process. They reported feeling more motivated to participate in project activities. However, several students also mentioned challenges such as the need for more intensive guidance, differences in group members’ discipline, and project-related costs that they considered burdensome. Overall, students’ perceptions of this learning model are positive, as it is viewed as effective in enhancing understanding, participation, and character development in alignment with the goals of the P5 program.